Social support for adolescents at risk of school failure - Richman, Jack M.; Bowen, Gary L.; Rosenfeld, Lawrence B. (1998)
Social support, widely studied as a variable that positively affects the adaptation of adolescents, is often less present in the lives of youths at risk of school failure. This study explores the social support of at-risk students, including who provides each of eight types of support, and the effects of particular types of social support on school performance outcomes. Results of analyses of data from students enrolled in Communities in Schools programs, indicate that parents and adult caretakers are major sources of social support for both middle and high school at-risk students. Analyses of school outcomes data indicate that particular types of social support are associated with different desirable school outcomes. The article presents implications for social work practice and the development of intervention strategies to enhance students' school performance and behavior. - Reproduced
Keywords: Adolescence; Schools